2010
DOI: 10.1155/2010/382301
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of Repeat Capsule Endoscopy and the Effect on Subsequent Patient Management

Abstract: Due to the high diagnostic yield and noninvasive nature of CE, repeat CE appears to be of benefit and should be considered for specific patients before other types of small bowel studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
4
11
0
1
Order By: Relevance
“…A role for repeat capsule endoscopy has also been suggested, with recent studies showing diagnostic yield of 20-75%, depending on the reason for the repeat exam. 25,26 In addition, endoscopic techniques of visualizing the deep small bowel have improved over recent years; most notably, double-balloon enteroscopy allows the potential for endoscopic visualization of the entire small bowel. The diagnostic yield of double-balloon enteroscopy is comparable to that of wireless capsule endoscopy, and in some studies exceeds the sensitivity of wireless capsule endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…A role for repeat capsule endoscopy has also been suggested, with recent studies showing diagnostic yield of 20-75%, depending on the reason for the repeat exam. 25,26 In addition, endoscopic techniques of visualizing the deep small bowel have improved over recent years; most notably, double-balloon enteroscopy allows the potential for endoscopic visualization of the entire small bowel. The diagnostic yield of double-balloon enteroscopy is comparable to that of wireless capsule endoscopy, and in some studies exceeds the sensitivity of wireless capsule endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, VCE does miss clinically important duodenal and proximal jejunal lesions (64)(65)(66)(67), and thus cannot be solely relied upon for exclusion of bleeding lesions in these areas. However, there are studies to suggest that repeat VCE may be of benefi t and increase the diagnostic yield, even when the fi rst study is negative (68)(69)(70). A prospective study again showed that repeat VCE may be beneficial, particularly when the bleeding changes from occult to overt or there is a hemoglobin drop ≥4 g/dl ( 71 ).…”
Section: Push Enteroscopymentioning
confidence: 99%
“…In patients with negative CE who have ongoing or recurrence of obscure bleeding, repeat investigations can yield positive findings and result in a change in management. [72][73][74][75] In RCTs comparing different capsules in patients who underwent 2 consecutive CE examinations, discordant results between the 2 CE procedures were reported in approximately 16% of cases. 76,77 In a small cohort study, the diagnostic yield of the single CE was 37.5% for the first CE, 43.8% for the second CE, and 62.5% for the combined findings of the back-to-back CEs within a 24-hour interval.…”
Section: Gastrointestinal Bleedingmentioning
confidence: 99%